The Tax Audit Management, Tax Control Mechanisms, and the Performance of State Internal Revenue Services in South-West, Nigeria - Olumoh, Yusuf Alabi; Mubaraq, Sanni (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The development of any nation is closely tied to its ability to generate and allocate revenue effectively, particularly for public infrastructure and services. In Nigeria, rising government expenditures and dwindling revenues have pushed state governments to explore strategies for improving their revenue base. Among the most critical of these strategies are efficient tax audit management and robust tax control mechanisms. Despite their importance, low tax compliance and high tax evasion continue to challenge the effectiveness of tax systems. This study examines the relationship between tax audit management, tax control mechanisms, and the performance of State Internal Revenue Services (SIRS) in South-West Nigeria. It specifically investigates how these two constructs impact SIRS performance across six states: Lagos, Ogun, Oyo, Osun, Ondo, and Ekiti. A cross-sectional survey design was employed, using structured questionnaires administered to 383 randomly selected respondents from a population of 8,771 management staff. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to estimate the relationships among the study variables. The study concludes that tax audit management and tax controls enhance SIRS performance significantly, thereby enhancing efficiency and compliance. The study therefore recommends that tax authorities strengthen tax audit management practices by implementing more effective strategic audit plans, ensuring consistent case tracking, and maintaining audit independence through risk-based reviews. More focus and emphasis should be placed on back-duty audits, proper documentation, and structured compliance processes. SIRS should conduct regular evaluations, integrate risk management, and align controls with international standards.